The Contribution of the Cerebellum to Cognition in Spinocerebellar Ataxia Type 6 - Freya E. Cooper; Manon Grube; Kelly J. Elsegood; John L. Welch; Thomas P. Kelly; Patrick F. Chinnery; Timothy D. Griffiths (Behavioural Neurology)
This study sought evidence for a specific cerebellar contribution to cognition by characterising the cognitive phenotype of Spinocerebellar Ataxia Type 6 (SCA-6); an autosomal dominant genetic disease which causes a highly specific late-onset cerebellar degeneration. A comprehensive neuropsychological assessment was administered to 27 patients with genetically confirmed SCA-6. General intellectual ability, memory and executive function were examined using internationally standardised tests (Wechsler Adult Intelligence Scale-III, Wechsler Memory Scale-III, Delis and Kaplan Executive Function System, Brixton Spatial Anticipation test). The patient group showed no evidence of intellectual or memory decline. However, tests of executive function involving skills of cognitive flexibility, inhibition of response and verbal reasoning and abstraction demonstrated significant impairment at the group level with large effect sizes. The results demonstrate an executive deficit due to SCA-6 that can be conceptualised as parallel to the motor difficulties suffered by these patients: the data support a role for the cerebellum in the regulation and coordination of cognitive, as well as motor processes that is relevant to individual performance.